The association of maternal serum CRP level with gestational diabetes mellitus - Haque, Nadira; Nahar, Khairun; Hoque, Moinul; Rauniyar, Neha; Aziz, Tabinda Anjum; Haque, Shakila; Khaleda, Laila; Tithi, Shaila Sharmin; Koly, Homayera (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Gestational diabetes mellitus is a common medical condition during pregnancy that has detrimental effects on maternal health and fetal well-being. Many serum markers are known to be associated with gestational diabetes, a subclinical inflammatory state that liberates inflammatory mediators, acute phase proteins like CRP into the maternal circulation. This phenomenon has invited many researchers to study inflammatory mediators and acute phase proteins as markers of gestational diabetes mellitus.This case-control study was conducted in the Department of Obstetrics and Gynecology of Bangabandhu Sheikh Mujib Medical Univer- sity, Dhaka, between July 2016 and June 2017. The objective of the study was to evaluate the association of serum CRP level with gestational diabetes mellitus. A total of 140 pregnant women who attended the out-patients antenatal clinic at their 2nd and 3rd trimester (13-40 weeks) of pregnancy were enlisted for the study. The case group consisted of 70 pregnant women who were diagnosed with GDM. Similar number of healthy pregnant women were recruited as control. GDM was diagnosed using standard 75 g OGTT. Blood sample was taken from study subjects to estimate the serum CRP level. CRP level up to 5mg/L was taken as normal. Data analysis was done by utilizing SPSS version 16. The mean BMI of the case group women was significantly higher than the mean BMI of the control (p=0.001). The mean CRP level in case was 13.87±10.19 and the mean for CRP for control group was 4.59±2.41. There was an association of raised level of CRP with GDM. Pregnant mothers with raised level of CRP (& gt; 5 mg/L) were 6.1 times more likely to have GDM than mothers with normal level of CRP. The study concluded that a significant association was found between the raised level of CRP and gestational diabetes mellitus. BSMMU J 2022; 15(2): 96-101